Right within : how to heal from racial trauma in the workplace - Harts, Minda (Seal Press, 2021)
"In these tumultuous times, as workplaces across the nation struggle to become truly inclusive, women of color need frank talk and honest advice on how to deal with microaggressions, how to heal from racialized trauma, how to find relief from invisible workplace burdens. The stakes are high, as even Lauryn Hill had put it: "How you gonna win when you ain't right within?" In Right Within, Harts offers essential self-help guidance for readers to learn to steady themselves, steer their outlook, and find much-needed joy at work. Filled with Harts's signature wit and warmth, Right Within offers strategies for women of color to build confidence, banish imposter syndrome, and move beyond past triggers they may not even know still cause pain. She encourages women of color to advocate for themselves effectively, and also helps reframe the challenges they face, to refocus past career disappointments into opportunities to move forward. Harts not only shares stories and wisdom gained from her personal journey, but she includes advice from therapists and faith leaders on a full range of ways to heal. Through her company The Memo, Minda Harts has worked with Fortune 500 companies to offer guidance and support for women of color on the rise. Here, through action points and clear-eyed coaching, Harts offers the roadmap to summoning hidden reserves of strength and courage. The path ahead can require hard internal work, but it's worth it if this enables readers to breathe freer and feel more like themselves at work. And in the end, Right Within will help women of color strengthen their voices and resolve across corporate America, ensuring that we can all, finally, rise together"--